Influence of non-woven fleece on the yield formation of early potatoes - K. Hamouz; J. Lachman; P. Dvořák; E. Trnková (Plant, Soil and Environment, 2006)
In the years 1999-2003 the effect of covering rows of early potatoes with non-woven fleece on the yield formation, dry matter content in tubers, temperature of soil and of air in ground layer was investigated. Covering of rows enhanced the market yield of tubers at early harvest 60 days after planting in average by 35.8% in comparison with the uncovered control. At harvest 67 days after planting the difference in advantage of the covered variant were 17.2% and 85 days after planting the difference in yield between variants was already non significant. The yield effect of the fleece was affected by year (higher effect in the years with cold spring) and by variety (Impala responded at 60 days after planting by yield increase under fleece 43.7%, Adora 27.9%). Higher dry matter content of tubers by 0.87% was found in covered plants 60 days after planting in comparison with control. Cover enhanced average air temperature in ground layer by 2.0°C, in soil in depth 100 mm by 1.8°C.